Isolation and Purification of Raw Starch Degrading Enzyme from Endophytic Fungi and its Application for Glucose Production - Marlida, Yetti (2001)
Raw starch degrading enzymes are enzymes that degrade polymers of raw starches to smaller molecules of oligo saccharides. Fifty-two strains of endophytic fungi were isolated from tropical plant trees in Malaysia and screened for raw starch degrading enzyme activity. Twelve endophytic strains with the ability to degrade raw starches as indicated by size of clear zone formed on Czapek-Dox medium were obtained. Three strains were found to be good raw starch degrading enzyme producers based on the ability to degrade raw starches. Raw sago, potato and rice starches were found to be appropriate substrate for enzyme production. The three strains of endophytic fungi were identified as Gibberella pulicaris using 18S rRNA sequences and, Acremonium sp. and Synnematous sp. taxonomically, respectively. Comparison of their degradative activity on raw and gelatinized starches, substrate specificity, optimum pH and product of hydrolysis showed that Acremonium sp. had a broad activity towards both small and large sized granules of raw starches while G. pulicaris and Synnematous sp. were dependent on the granule size and structures of starches. The enzyme from Acremonium sp. is unique since it does not depend on the granule size and structures of starches. The results showed that the enzyme from G. pulicaris and Acremonium sp. were raw starch degrading glucoamylase, an exo-acting enzyme which solely yielded glucose while enzyme from Synnematous sp. was raw starch degrading a-amylase, an endo-acting enzyme which yielded a mixture of glucose and maltose. Consequently, raw starch degrading glucoamylase was more efficient than raw starch degrading a-amylase. Both glucoamylase and a-amylase showed the highest degradation rate on raw rice starch. Based on the substrate specificity, degradative pattern and product produced, the Acremonium sp. was selected and pursued to produce raw starch degrading enzyme. The optimum conditions for enzyme production based on carbon and nitrogen sources were studied. Results showed that the highest raw starch degrading enzyme activity was observed when the Acremonium sp. were grown in shake flask culture of broth medium at 120 rpm, 30°C for 5 days and yielded glucoamylase activity of 67 U/ml. The enzyme was induced in broth medium by the addition of raw sago starch as its carbon source and peptone and sodium nitrate as nitrogen sources. Acremonium sp. showed maximum enzyme activity when grown at pH 5.0, 30°C for 5 days. The raw starch degrading enzyme was found to be inducible enzymes depending on the amount of raw sago starch added to the culture medium. The raw starch degrading enzyme from Acremonium sp. was purified to homogeneity by a combination of ultrafiltration, DEAE-Toyopearl 650 S ion exchange and Sephadex G-150 gel filtration. Pure raw starch degrading enzyme was shown to consist of two sub-units of 22 and 39 kDa by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and a single band on native-polyacrylamide gel electrophoresis. The optimum pH and temperature for hydrolysis of raw starches were 5.5 and 55°C,respectively. The enzyme was stable at pH range of 3.0 to 7.0 and at temperature up to 60°C. The purified enzyme had Km values of 10.0 and 3.8 mg/ml and V max of 195 µmoles/ml/min and 391 µmoles/ml/min for amylose and amylopectin, respectively. Pretreatment of sago starch at low pH and heating below gelatinization temperature was found to increase the enzymatic hydrolysis.